Biochemical characterization of patients with dihydrolipoamide dehydrogenase deficiency - Parith Wongkittichote; Sanmati R. Cuddapah; Stephen R. Master; Dorothy K. Grange; Dennis Dietzen; Stephen M. Roper; Rebecca D. Ganetzky (JIMD Reports, 2023)
Abstract Dihydrolipoamide dehydrogenase (DLD; E3) oxidizes lipoic acid. Restoring the oxidized state allows lipoic acid to act as a necessary electron sink for the four mitochondrial keto‐acid dehydrogenases: pyruvate dehydrogenase, alpha‐ketoglutarate dehydrogenase, branched‐chain α‐keto‐acid dehydrogenase, and 2‐oxoadipate dehydrogenase. DLD deficiency (DLDD) is caused by biallelic pathogenic variants in DLD. Three major forms have been described: encephalopathic, hepatic, and myopathic, although DLDD patients exhibit overlapping phenotypes. Hyperlactatemia, hyperexcretion of tricarboxylic acid cycle (TCA) metabolites and branched‐chain keto acids, increased plasma branched‐chain amino acids and allo‐isoleucine are intermittent metabolic abnormalities reported in patients with DLDD. However, the diagnostic performance of these metabolites has never been studied. Therefore, we sought to systematically evaluate the diagnostic utility of these biomarkers for DLDD. We retrospectively analyzed the results of biochemical testing of six unrelated DLDD patients, including values obtained during both well visits and acute decompensation episodes. Elevation of branched‐chain amino acid concentrations was not consistently observed. We found that five of six patients in our cohort had a maximum lifetime value of allo‐isoleucine of 6 μmol/L, showing that alloisoleucine elevations even during illness may be subtle. Urine organic acid analysis (UOA) during acute decompensation episodes was abnormal in all cases; however, the pattern of abnormalities had high intersubject variability. No single biomarker was universally present, even in patients experiencing metabolic decompensation. We also observed novel biochemical associations: three patients had hyperexcretion of TCA cycle metabolites during crisis; in two patients, 2‐ketoadipic and 2‐hydroxyadipic acids, by products of lysine degradation, were detected. We propose that these result from 2‐oxoadipate dehydrogenase deficiency, an underappreciated biochemical abnormality in DLD. Given the diversity of biochemical profiles among the patients with DLDD, we conclude that accurate biochemical diagnosis relies on a high index of suspicion and multipronged biochemical analysis, including both plasma amino acid and urine organic acid quantitation during decompensation. Biochemical diagnosis during the well state is challenging. We emphasize the critical importance of multiple simultaneous biochemical tests for diagnosis and monitoring of DLDD. We also highlight the under‐recognized role of DLD in the lysine degradation pathway. Larger cohorts of patients are needed to establish a correlation between the biochemical pattern and clinical outcomes, as well as a genotype–phenotype correlation.